Does weight loss improve semen quality and reproductive hormones? results from a cohort of severely obese men - Ernst Emil; Bungum Mona; Andersen Claus; Bonde Jens; Olsen Jørn; Aggerholm Anette; Thulstrup Ane; Håkonsen Linn; Hansen Mette; Ernst Erik; Ramlau-Hansen Cecilia (BMC, 2011)
Abstract Background A high body mass index (BMI) has been associated with reduced semen quality and male subfecundity, but no studies following obese men losing weight have yet been published. We examined semen quality and reproductive hormones among morbidly obese men and studied if weight loss improved the reproductive indicators. Methods In this pilot cohort study, 43 men with BMI > 33 kg/m2 were followed through a 14 week residential weight loss program. The participants provided semen samples and had blood samples drawn, filled in questionnaires, and had clinical examinations before and after the intervention. Conventional semen characteristics as well as sperm DNA integrity, analysed by the sperm chromatin structure assay (SCSA) were obtained. Serum levels of testosterone, estradiol, sex hormone-binding globulin (SHBG), luteinizing hormone (LH), follicle-stimulating hormone (FSH), anti-Müllerian hormone (AMH) and inhibin B (Inh-B) were measured. Results Participants were from 20 to 59 years of age (median = 32) with BMI ranging from 33 to 61 kg/m2. At baseline, after adjustment for potential confounders, BMI was inversely associated with sperm concentration (p = 0.02), total sperm count (p = 0.02), sperm morphology (p = 0.04), and motile sperm (p = 0.005) as well as testosterone (p = 0.04) and Inh-B (p = 0.04) and positively associated to estradiol (p < 0.005). The median (range) percentage weight loss after the intervention was 15% (3.5 - 25.4). Weight loss was associated with an increase in total sperm count (p = 0.02), semen volume (p = 0.04), testosterone (p = 0.02), SHBG (p = 0.03) and AMH (p = 0.02). The group with the largest weight loss had a statistically significant increase in total sperm count [193 millions (95% CI: 45; 341)] and normal sperm morphology [4% (95% CI: 1; 7)]. Conclusion This study found obesity to be associated with poor semen quality and altered reproductive hormonal profile. Weight loss may potentially lead to improvement in semen quality. Whether the improvement is a result of the reduction in body weight per se or improved lifestyles remains unknown.